The continuous hydrolysis of geniposide to genipin using immobilized β-glucosidase or calcium alginate gel - FUJIKAWA, S; YOKOTA, T; KOGA, K; KUMADA, J.-I (Biotechnology letters, 1987)
The reaction velocity of immobilized beta -glucosidase was approximated by the first-order reaction kinetics. A plug flow reactor was used for continuous hydrolysis of geniposide with this immobilized enzyme. The activity of this immobilized enzyme was retained 100% for 600 h. The amount of genipin formed by using the immobilized enzyme was 17 fold that formed using the native enzyme without reuse. Using immobilized enzyme, purity and yield of genipin, which is a hydrolyzate of geniposide, was improved comparing with the native enzyme.